2021
DOI: 10.1111/jam.15092
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid detection Aspergillus fumigatus by loop‐mediated isothermal amplification coupled with lateral flow biosensor assay

Abstract: Aims:We have developed a new diagnostic technique, termed loop-mediated isothermal amplification coupled with lateral flow biosensor (LAMP-LFB), which has been successfully applied to the detection of Aspergillus fumigatus. Material and Methods: A set of six LAMP primers was designed according to the A. fumigatus-specific anxC4 gene, which specifically recognized eight different regions of the target sequence. The LFB was employed for reporting the A. fumigatus-LAMP results, and the visual readouts were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…LAMP offers a rapid and high throughput alternative for detection of several types of disease-causing fungi viz. Candida albicans, Cryptococcus neoformans and Mucor racemosus ( Nakayama et al., 2017 ) , Trichosporonasahii ( Zhou et al., 2015 ), Aspergillus fumigatus ( Jiang et al., 2021 ) , Pythium insidiosum ( Htun et al., 2020 ) , etc. These studies have shown the requirement of a very low amount of DNA for LAMP assay which shows the high sensitivity of this method.…”
Section: Diagnostic Applications Of Conventional Lampmentioning
confidence: 99%
“…LAMP offers a rapid and high throughput alternative for detection of several types of disease-causing fungi viz. Candida albicans, Cryptococcus neoformans and Mucor racemosus ( Nakayama et al., 2017 ) , Trichosporonasahii ( Zhou et al., 2015 ), Aspergillus fumigatus ( Jiang et al., 2021 ) , Pythium insidiosum ( Htun et al., 2020 ) , etc. These studies have shown the requirement of a very low amount of DNA for LAMP assay which shows the high sensitivity of this method.…”
Section: Diagnostic Applications Of Conventional Lampmentioning
confidence: 99%
“…Lateral flow strips from different manufacturers-Millenia [197,234,235], Foresite Diagnostics [230,233,236], Biohelix [229], and AMODIA Bioservice [237]-were implemented for the detection of labelled amplicons. Additionally, homemade dipsticks utilizing NP-streptavidin conjugate were used [237].…”
Section: Lamp-based Testsmentioning
confidence: 99%
“…Lateral flow strips from different manufacturers-Millenia [197,234,235], Foresite Diagnostics [230,233,236], Biohelix [229], and AMODIA Bioservice [237]-were implemented for the detection of labelled amplicons. Additionally, homemade dipsticks utilizing NP-streptavidin conjugate were used [237]. Different approaches were designed to obtain labelled products, including FIP/BIP-labelled primers [229,236], FIP-/loop-labelled primers [237], loop-labelled primers [230,233], and biotin-labelled probes for hybridization of FITC-labelled amplicon [197,234,235].…”
Section: Lamp-based Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, isothermal amplification assays showed great potential in scientific and clinical research [ 26 ]. Loop-mediated isothermal amplification (LAMP) is one of the well-recognized isothermal amplification techniques applied in clinical diagnosis [ 27 , 28 ]. But LAMP needs specific design of 2 to 3 pairs of primers and the processes of primer design and selection are tedious [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%